Media Framing of Political Instability and its Impact on Developmental Policies in West Africa - Abwami, Innocent, Michael; Shahid, Jennifer Iheanacho (African Journal of Stability and Development (AJSD), 2024)
This study explored the media framing of political instability in West Africa and its consequent impact on developmental policies. The media’s role in shaping public perceptions of political events was investigated, revealing that the portrayal of instability often influences the policy-making process. By employing a qualitative analysis of various media sources, the study examined how narratives around political unrest affect public opinion and government responses. The findings indicated that sensationalised media coverage exacerbate fear surrounding instability, leading to reactive policy measures rather than proactive strategies for development. Moreover, the research highlighted the interplay between media representations and governance, demonstrating how the framing of instability not only reflects societal anxieties but also shapes the political landscape. The study concluded that a more responsible media approach is essential for fostering informed public discourse and promoting sustainable development in the region